Анализ экспериментальных данных по моделированию уровенного режима каскадов водохранилищ при возникновении аварийных ситуаций - Levkevich Виктор; Pastukhov Сергей (Vestnik of the Institute for Command Engineers of the MES of the Republic of Belarus, 2010)
Based on the water level variation modeling of tandem reservoir system in consideration of different reservoir system arrangement and hydrodynamic disaster initiation scenarios the water level raising (recession) rate quantitative data for any step of tandem is presented. The detailed analysis of dirt fillings wash-out used as idle spillway as far as closure channel of dam initiation in case of upstream face disruption analysis are carried out. The water level variation modeling was conducted in consideration of 10%, 5% and 1% weir flow probability. The tandem reservoir system arrangement safety criterion is developed and validated.